Lean Management Genesis = Geneza Lean Management - Parkes, Aneta (Zielona Góra: Faculty of Economics and Management Press)
Lean Management is a philosophy and management concept, based on reduction of the waste and resources used in the process of producing goods and providing services. Lean Management genesis dates back to scientific management in America (for example concepts of H. Ford and F.W. Taylor) and quality management, including development of TQM concept.
Keywords: lean management; zarządzanie naukowe; zarządzanie przez jakość; TPS; droga Toyoty; kultura lean management; scientific management; TQM; Toyota Way; lean management culture